Slum Tourism: Representing and Interpreting Reality in City - Tatang Rusata; Genardi Atmadiredja; Ainnoun Kornita (Indonesian Journal of Tourism and Leisure, 2023)
Slum areas are often seen in urban spatial policy gaps. The slum area becomes a dilemma, it portrays the unsuccessful management of a city area, on the other hand the reality of the city has the potential to become slum area tourism as an alternative attraction for tourism in urban areas.  Efforts made by stakeholders in terms of city management tend to ignore slum areas as a city reality that has never touched a solution to the problem. Slum areas with social problems require real solutions.  Through tourism in slum areas, residents innovate to represent and interpret their territory to find solutions for themselves. So far, studies on slum area tourism regarding how local residents represent and interpret their territory are still rare. Therefore, this study tries to look at the initiative to practice representation and interpretation of local residents in their area, and how stakeholders represent slum areas in their area through a qualitative study using a city tourism approach. Based on the results of data collection, a description of the situation of slum areas and their communities can practically represent themselve as the reality of the city and present themselve as part of the development of city tourism. By imaging the slum area, local people earn income from interacting with tourists who hope to get a complete experience of the city's tourist destinations they visit. On the other hand, local communities who are involved in the practice of representing slum area tourism indirectly criticize city management by displaying the contrast between slum area residents and tourists through digital media within the framework of local initiatives as a form of development participation.